Um olhar sobre o corpo nos salões: das festas de brega aos floreios - SILVA, Mayra Nascimento (2019)
This research has as object of study the difference of bodies dancing tacky at parties and ballroom dancing balls Cia Cabanos in Belém do Pará. As theoretical frameworks use me Daolio, Geertz, Gehlen, Mauss, Roberts, Perna, Bueno , Toneli Mosque, Miller and with respect to the tacky resorted to coast. As analysis methodologies bring the comparative methods and case study. Realized interview free narrative, such as data collection technique with Rolon Ho, said gym owner and other members of Cia Cabanos. As a result present the flourishes of tacky that are specific to the ballroom dancing and that are not present in the bodies that are at parties.